Presence and health risks of obsolete and emerging pesticides in paddy rice and soil from Thailand and China - Naranun Khammanee (2020)
© 2020 by the authors. Licensee MDPI, Basel, Switzerland. Organochlorine (OCPs) and organophosphorus pesticides (OPPs) have been intensively applied in rice paddy field farming to control pest infestation and increase the yield. In this study, we investigated the presence of organochlorine and organophosphorus pesticides in paddy rice and soil from rice plantations in Thailand and China. According to concentration and distribution of OCPs, the most abundant OCPs residues in rice and soil from Thailand and China were dichlorodiphenyltrichloroethane and hexachlorocyclohexanes. The OPPs of methidathion, carbophenothion, chlorpyrifos, and diazinon were common to Thailand and China in both types of samples. The detection frequency of multiple types of these pesticides was greater than 50% of total samples. The relative concentration of some OPPs residues in rice and soil from Thailand and China were significantly different from each other (p < 0.0083), whereas, no significant difference was observed for the relative concentration of OCPs residues in rice and soil from both countries, except for HCHs (p < 0.05). Bioaccumulation factors of OCPs between rice and soil samples indicated that OCPs and OPPs in soil could accumulate in rice. The carcinogenic and noncarcinogenic risks of OCPs and OPPs seem to be in the safe range as recommended by the European Union.